The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1016/s1001-0742(08)62127-0
|View full text |Cite
|
Sign up to set email alerts
|

Phototransformation of nitrobenzene in the Songhua River: Kinetics and photoproduct analysis

Abstract: Nitrobenzene (NB) pollution of the Songhua River caused by an explosion at a petrochemical plant in Jilin City, Jilin Province, China, attracted public concern over the fate of NB in the river. As one of the efforts to predict the fate of residual NB in the river, the kinetics and mechanism of phototransformation of NB in natural water from four sections of the Songhua River were investigated. It was found that photodegradation of NB in water proceeded via pseudo-first-order reaction kinetics under simulated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…Analysis by GC/MS showed the presence of phenol, nitrophenols, dinitrophenol, and one of the isomers of azobenzene in the final solution. The results are in accordance with the results of previous researchers (Wang et al 2008;Kochany 1992;Miguel et al 2000). Fendler and Gasowski (1968) suggested that the enhanced conjugation of the nitro group with benzene ring might be responsible for the selective activation of the ortho and para positions of nitrobenzene (NB).…”
Section: Oxidation Of H 2 Osupporting
confidence: 93%
“…Analysis by GC/MS showed the presence of phenol, nitrophenols, dinitrophenol, and one of the isomers of azobenzene in the final solution. The results are in accordance with the results of previous researchers (Wang et al 2008;Kochany 1992;Miguel et al 2000). Fendler and Gasowski (1968) suggested that the enhanced conjugation of the nitro group with benzene ring might be responsible for the selective activation of the ortho and para positions of nitrobenzene (NB).…”
Section: Oxidation Of H 2 Osupporting
confidence: 93%
“…The JUA covers 1267.89 km 2 and is located between 4840,000 and 4905,000 north and 260,000 and 320,000 east in the central of Jilin Province, China ( Figure 1). JUA has a population of 1.60 million and is an important irrigation and industrial district of China.…”
Section: Study Areamentioning
confidence: 99%
“…The area of JUA is 1267.89 km 2 and it is assumed to be a rectangular shape. The grid cells were designated as "inactive" outside the model domain and as "active" inside the model domain.…”
Section: Model Discretizationmentioning
confidence: 99%
“…Thus, volatilization should be one of the main processes responsible for the loss of NB from river water. On the other hand, photolysis could also be responsible for the loss of NB (Wang et al, 2008).…”
Section: Contribution Of Biodegradation To the Loss Of Nb Flux Duringmentioning
confidence: 99%
“…For controlling the losses and impact of the accident at a level as low as possible, the government started a wide range of investigations to understand the behavior and fate of residual NB in the river. Evaluation of NB degradation abilities of microbes at different river sections was one of the main tasks of the investigation Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%